Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given an expression, for example, $$f(x,y)=\frac{x}{(x-1)(1-y)(xy+x-1)}$$

How can we find the general expression involving $m$ and $n$ for $$\lim_{x\to 0, y\to 0}{\frac{\partial^{n+m}{f}}{\partial{x}^{m}\partial{y}^{n}}}$$

share|improve this question
    
Have you considered expanding into power series of $x$ and $y$? –  Shai Covo Feb 17 '11 at 21:30
    
@Shai, yes, but how to do it in details? Can you please give the details as well as the final answer? –  Qiang Li Feb 17 '11 at 21:37
    
I just wanted to know whether you considered that; I haven't thought about the details... –  Shai Covo Feb 17 '11 at 21:44
    
Why is the final answer so important? Given the method, you could find the answer for this question, as well as for similar ones in the future. –  Yuval Filmus Feb 18 '11 at 6:16
add comment

1 Answer 1

up vote 1 down vote accepted

Suppose $f = \sum_{i,j \geq 0} c_{ij} x^i y^j$. The limit you're looking for is $m!n! c_{mn}$. Your function is better written as $$f(x,y) = \frac{x}{(1-x)(1-y)(1-x-xy)},$$ where the most interesting factor is $$\frac{1}{1-x-xy} = \sum_{t \geq 0} x^t(1 + y)^t = \sum_{t,s \geq 0} \binom{t}{s} x^t y^s.$$ Multiplying by a variable $1/(1-z)$ is like taking "running sums" across $z$. So $$\frac{x}{(1-x)(1-y)(1-x-xy)} = \sum_{t,s \geq 0} x^{t+1} y^s \left[ \sum_{T \leq t, S \leq s} \binom{T}{S} \right]. $$ So the value you're looking for is $$m!n!\sum_{T \leq m-1,S \leq n} \binom{T}{S}.$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.